Use of alcoholic beverages in VA medical centers - Qadri S Faiz; Sattar S Pirzada; Warsi Mustafa K; Okoye Cordelia; Din Amad U; Padala Prasad R; Bhatia Subhash C (BMC, 2006)
Abstract Background Benzodiazepines are the first-line choice for the treatment of alcohol withdrawal syndrome. However, several hospitals continue to provide alcoholic beverages through their formulary for the treatment of alcohol withdrawal. While there are data on the prevalence of this practice in academic medical centers, there are no data on the availability of alcoholic beverages at the formularies of the hospitals operated by the department of Veteran's Affairs. Methods In this study, we surveyed the Pharmacy managers at 112 Veterans' Affairs Medical Centers (VAMCs) to ascertain the availability of alcohol on the VAMC formularies, and presence or lack of a policy on the use of alcoholic beverages in their VA Medical Center. Results Of the pharmacy directors contacted, 81 responded. 8 did not allow their use, while 20 allowed their use. There was a lack of a consistent policy across the VA medical centers on availability and use of alcoholic beverages for the treatment of alcohol withdrawal syndrome. Conclusion There is lack of uniform policy on the availability of alcoholic beverages across the VAMCs, which may create potential problems with difference in the standards of care.